Heterosis F1 Hibrida dan Daya Gabung Galur Mandul Jantan dari Tiga Tipe Sitoplasma dan Galur Pemulih Kesuburan Padi (Oryza sativa L.) - Widyastuti, Yuni; Purwoko, Bambang sapta; Yunus, Muhammad; Kartina, Nita; Wibowo, Bayu Pramono; Rumanti, Indrastuti Apri; Satoto, Satoto (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
The combining ability provides information on parental lines selection and F1 hybrids having high yield potential. The analysis important to evaluate new parental lines used at hybrid rice breeding. The objectives of the research were to study combining ability of line (CMS/A) and tester (Restorer/R) in producing the new hybrid rice, and to evaluate those new hybrid performance. The research was conducted in November in 2014 to February in 2015 at Indonesian Center for Rice Research field station, in Sukamandi. Mating design and analysis were done using line x tester design. Thirty hybrids and their parental lines were planted in the field using randomized complete block design with three replications. The characters of yield and yield components were observed. Among the lines, CMS IR 58025A was a good general combiner for number of filled grain per panicle, while GMJ 14A was a good general combiner for maturity, and seed set. Among the testers, PK 12 line was the best general combiner for maturity and seed set, while BP 11 was the best general combiner for number of filled grain per panicle. The new hybrid rice with high specific combining ability for grain weight per hill were GMJ 13A/PK 90 (WA), IR 80154A/R 32 (Gambiaca), and GMJ 14A/R 3 (Kalinga). The hybrids rice with the highest standard heterosis compared than Maro and Ciherang, were GMJ 13A/BP 11, GMJ 14A/PK 90, and GMJ 15A/PK 90, each with CMS with genetic background group of WA, Kalinga, and Gambiaca, respectively.